Efektifitas Model "PC-JeWa" Perawat terhadap Loyalitas Pasien Rawat Inap - Saragih, Enni Juliani; Utami, Ressa Andriyani (Jurnal Kesehatan Holistic, 2020)
Caring behavior is an absolute thing that nurses must do to patients. The objective of this study were to determine the effectiveness of caring caring behaviors towards hospital inpatient loyalty. This study used a qualitative method of cross-sectional approach with a total sample of 100 people taken through random sampling. The results showed that nurses caring behavior significantly related to patient satisfaction (p value 0,000, OR = 11,769). Patient satisfaction was also significantly related to patient loyalty (p value 0,000, OR = 6,328). Caring behavior was significantly related to patient loyalty (p value 000, OR = 9,913). The dominant nurse caring behavioral dimensions are: helping meet patient needs according to the ability and disability of the patient (for example: eating, drinking, defecating, urinating, changing clothes and others) with a beta coefficient value (OR = 3.114). Nurses who work in services should optimize the fulfillment of basic needs to increase patient loyalty.